Alkaline xylanolytic–cellulolytic multienzyme complex from the novel anaerobic alkalithermophilic bacterium Cellulosibacter alkalithermophilus and its hydrolysis of insoluble polysaccharides under neutral and alkaline conditions. Issue 4 (April 2015) - Baramee, Sirilak; Phitsuwan, Paripok; Waeonukul, Rattiya; Pason, Patthra; Tachaapaikoon, Chakrit; Kosugi, Akihiko; Ratanakhanokchai, Khanok
Graphical abstract